Firm Level Innovation and Productivity: Is there a Common Story Across Countries? - Bettina Peters; Hans Lööf; Norbert Janz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Recent studies have documented extensive heterogeneity in firm performance within countries, and innovation has been found as an important determinant. This paper addresses the issue of innovation firm performance across countries. A growing number of national firm level studies on the innovation-productivity link have been conducted using new internationally harmonized survey data, known in Europe as Community Innovation Survey (CIS). Mainly due to confidentiality reasons cross-country comparisons of CIS data are still rare. The contribution of this paper is its unique approach of pooling original firm observations from Germany and Sweden. Applying a knowledge production function that gives the relationship between innovation input, innovation output and productivity, we find to a very large extent a common cross-country story for knowledge intensive manufacturing firms. Some interesting country-specific effects are reported as well.
Keywords: C34; P52; D24; O33; C51; 330; Innovation; Productivity; Cross-Country Comparison; Applied Econometrics; Innovation; Industrielle Forschung; Produktivität; Unternehmensentwicklung; Vergleich; Schätzung; Deutschland; Schweden